Hubungan Antara Konformitas Teman Sebaya Dengan Perilaku Merokok Pada Remaja Smk Al-Islam Surakarta - Sari, Riska Timur Ninditya; , Aad Satria Permadi, S.Psi, MA (2015)
Teens today have a lot to consume cigarettes. Stateteens who have started smoking often seemingly in the surrounding communities. It is very alarming, the condition of adolescent smoking behavior can adverse teens and others who are nearby. Has clearly written warning "Smoking kill" on cigarette packs. Many ads cigarette road, and a television that includes a warning tersebut.Namun, still many phenomena of young people smoking in society. One factor teens can be affected cigarette consumption one of which is conformity friends of the same age. The influence of the social environment is very influential in adolescents the onset of smoking behavior in adolescents. This research aims to determine the relationship between peer conformity with smoking behavior in adolescents. Researchers used quantitative methods to achieve the research objectives. Sample in this study were male students SMK Al-Islam Surakarta. The data in this study is the correlation test Product Moment The sampling technique used in a way proposive sampling, namely researchers determine the characteristics of the subject that is the subject of research. The number of subjects in this study were 75 male students of SMK Al-Islam Surakarta. Based on the results of the analysis are the results that the value of the correlation coefficient (r) amounted to 0.090 with significance (p) = 0.221; (P> 0.05), so the hypothesis denied, it means that there is no significant positive relationship between peer conformity with smoking behavior in adolescents SMK Al-Islam Surakarta. So it can be said there is no relationship between conformity peers and smoking behavior in adolescents SMK Al-Islam Surakarta. Variable conformity peers on the subject was moderate with a mean Empirical (RE) 24.93 and the mean hypothetical (RH) 27.5. Variable smoking behavior on the subject is low with average empirical (RE) 38.37 and the average hypothetic (RH) 50. Keywords: Conformity, Smoking Behavior